2015
DOI: 10.1007/s00586-015-4126-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost–utility of minimally invasive versus open transforaminal lumbar interbody fusion: systematic review and economic evaluation

Abstract: From the limited evidence, the available data suggest a trend of significantly reduced perioperative costs, length of stay, and blood loss for minimally invasive compared with open surgical approaches for TLIF. MI-TLIF may represent an opportunity for optimal utilization and allocation of health-care resources from both a hospital and societal perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…Most comparative studies currently available are retrospective [710]. Wong et al [10] compared 144 MI TLIF with 54 standard TLIF patients and found statistically significant benefits for MI TLIF in operating room time, blood loss, primary infection rates, secondary medical complications, LOS, transfusion need, hospital costs, short-term and long-term pain outcomes, and short-term and long-term ODI scores.…”
Section: Discussionmentioning
confidence: 99%
“…Most comparative studies currently available are retrospective [710]. Wong et al [10] compared 144 MI TLIF with 54 standard TLIF patients and found statistically significant benefits for MI TLIF in operating room time, blood loss, primary infection rates, secondary medical complications, LOS, transfusion need, hospital costs, short-term and long-term pain outcomes, and short-term and long-term ODI scores.…”
Section: Discussionmentioning
confidence: 99%
“…The statistics have been described elsewhere. 20 25 Briefly, the mean difference (MD) and relative risk (RR) were used as a summary statistic. In the present study, both fixed- and random-effect models were tested.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients with complications was 54 out of 455 (11.87%) in MIS TLIF versus 64 out of 446 (14.35%) in OPEN TLIF. 3 Costs: The direct hospital costs for each study were lower in MIS TLIF than in OPEN TLIF, associated with less blood loss, fewer days in the hospital, and fewer complications. 12 A financial analysis of the total direct hospital costs (blood, imaging, implant, drugs, physical/occupational or speech therapy, hospital stay) were lower in MIS TLIF than in OPEN TLIF, at USD 19,512 versus USD 23,550, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…1 Since Harms and Rolinger first described the procedure in 1982, OPEN TLIF has allowed circumferential arthrodesis and restoration of disc height, with a fusion rate of 95%, and has been considered a safe and effective option for the past 30 years. 3,4 The TLIF OPEN surgical technique consists of a standard incision in the midline with subperiosteal exposure of the musculature, exposing the facet joint complex to the distal space that is being fused in its entirety. A unilateral facetectomy is performed with the placement of an interbody cage and bilateral fixation with transpedicle screws.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation